Harvesting intensity versus sustainability in Indonesia - Sist, P.; Nolan, T.; Bertault, J.G.; Dykstra, D.P. (1998)
In East Kalimantan (Indonesia), impacts of conventional and reduced-impact logging (RIL) on forest ecosystems were compared on the basis of pre- and post-harvesting stand inventories. There was a positive and significant correlation between the proportion of trees damaged by felling and the density of trees felled. Logging intensity ranged from 1 to 17 trees ha- (9--247 m3 ha-1) and averaged 9 trees ha-1 (86.9 m3 ha-1). The study has shown that with RIL techniques, logging damage on the original stand can be significantly reduced by 50% compared with conventional logging. However, this 50% reduction in logging damage, was dependent on the felling intensity. With a felling intensity of 8 stems ha-1 or less, RIL techniques only damaged 25% of the original tree population whereas 48% were damaged with conventional techniques. Above this felling intensity (i.e. 8 stems ha-1), the effectiveness of RIL in limiting forest damage was significantly reduced, mainly because of the increasing felling damage. Moreover, the removal of all harvestable timber trees, leaving only few potential crop trees, will result in a seriously depleted residual stand. Because of the high damage involved by high felling intensity, leaving few potential crop trees, and the yield capacity of the remaining stand, acceptable harvesting volume will not be reached within the felling rotation of 35 years. It is concluded that silvicultural system based on diameter limit alone, as is the Indonesian system (TPTI), cannot be compatible with sustainability and more sophisticated harvested-selection rules are needed.